Effects of shape of the neck of classical acoustical resonators on the sound absorption quality for large amplitudes: Experimental results. Issue 2 (June 2020) - Gourdon, Emmanuel; Ture Savadkoohi, Alireza; Cauvin, Bertrand
This article presents some experimental results on Helmholtz resonators for large sound amplitudes with two general geometries of their necks: the resonators with classical (cylindrical) and quadratic nonlinear necks. Obtained results for large amplitudes show accelerated amplitude dependency of resonant frequencies of the resonators with modified shape of the neck compared to classical ones. This nonlinear response can be used as a passive controller system with nonlinear restoring forcing function for having broadband frequency absorption.